Effect of isovalent substitution on the structural and electrical properties of BixSb2-xTe3 topological insulator single crystals. (2020) - Anoop, M.D.; Yadav, Jyoti; Yadav, Nisha; Singh, Rini; Shinzato, K.; Dolia, S.N.; Jain, Ankur; Ichikawa, T.; Kumar, Manoj
Abstract: Isovalent doping is a well-known method to induce internal stress without altering the electronic structure of materials. This study aims at understanding the effect of isovalent substitution of bismuth with antimony on the structural and electrical transport properties in Bismuth Antimony Telluride (BST) systems. Single crystals of Bix Sb2-x Te3 (0 ≤ x ≤ 2) were synthesized using modified Bridgman technique. Morphological analysis and X-ray diffraction studies confirmed the formation of layered crystals in the R-3m phase for all the compositions. The lattice parameter a = b was found to increase consistently from x = 0 to x = 2 while c was found to decrease sharply between x = 1 and x = 1.5 . X-ray Photoelectron Spectroscopy (XPS) results confirm the formation of the nominal chemical compositions of the crystals. Temperature dependence of the resistivity of the crystals measured using the four-probe method was found to decrease with temperature for all the compositions. The single crystals with x = 1 show maximum resistivity throughout the temperature range. Interestingly, this composition shows a dip in the normal resistivity behaviour in the temperature range 90 K-120 K. Moreover, an upturn in the resistance was observed below 10 K for the compositions x = 1 and x = 1.5. It could be related to the dominance of electrical transport through topological surface states. Temperature dependence of the Hall coefficient indicates the majority of the carriers are a hole like except for the composition x = 1.5 . The composition with x = 1 shows the strongest temperature dependence of the Hall coefficient with a crossover from positive to negative in the temperature range between 90 K and 120 K. The results support the tuning of the Fermi level in the system by isovalent substitution.